Kinetics and Photodegradation Study of Aqueous Methyl tert-Butyl Ether Using Zinc Oxide: The Effect of Particle Size - Zaki S. Seddigi; Saleh A. Ahmed; Shahid P. Ansari; Ekram Danish; Abdullah Abu Alkibash; Shakeel Ahmed (International Journal of Photoenergy)
Zinc oxide of different average particle sizes 25 nm, 59 nm, and 421 nm as applied in the photodegradation of MTBE. This study was carried out in a batch photoreactor having a high pressure mercury lamp. Zinc oxide of particle size of 421 nm was found to be the most effective in degrading MTBE in an aqueous solution. On using this type of ZnO in a solution of 100 ppm MTBE, the concentration of MTBE has decreased to 5.1 ppm after a period of five hours. The kinetics of the photocatalytic degradation of MTBE was found to be a first order reaction.